Sistem Informasi Penstabilan Distribusi Sembako Pengendalian Inflasi pada Pasar Tradisional di Minahasa Utara - Reynoldus Andrias Sahulata (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
The increasing demand for basic necessities in North Minahasa, North Sulawesi, has not been matched by adequate supply, resulting in high inflation in three traditional markets: Airmadidi (28.5%), Sukur (24.3%), and Kauditan (32.5%). Price hikes indicate the urgent need for effective distribution strategies to stabilize staple food availability. Efforts to address this issue began with the immediate distribution of sufficient supplies, successfully reducing inflation to 18.5% in Airmadidi, 15.2% in Sukur, and 22.1% in Kauditan. Further improvements through continuous distribution lowered inflation to 3.2%, 2.8%, and 4.1% respectively. When supply eventually exceeded consumer demand, inflation rates shifted into deflation, recorded at -2.1% in Airmadidi, -1.8% in Sukur, and -2.5% in Kauditan. These results demonstrate that systematic and sustainable supply chain management can effectively stabilize market conditions. The study was conducted between January 2024 and May 2025, using data from the Central Statistics Agency (BPS) of North Sulawesi in the form of the Consumer Price Index (CPI/IHK), complemented by data from the Minahasa Regency Trade Office, and field surveys and interviews with 50 traders in each market. Based on these findings, an Information System for Stabilizing the Distribution of Staple Foodstuffs and Controlling Inflation in Traditional Markets in North Minahasa is proposed as a strategic solution to support regional economic stability.